Spatial and temporal variation in precipitation at the start of the rainy season in tropical Australia - Garnett, S.T; Williamson, G (The Rangeland journal, 2010)
The patterns of rainfall early in the rainy season vary substantially across northern Australia, even in sites with the same annual average. This has biophysical and economic implications in terms of land and infrastructure management, resource availability and capacity, and access. Daily patterns in long-term rainfall records in Australia north of 23°S subject to regular monsoonal rainfall were compared with threshold levels for dryland and wetland seed germination, initiation of the growing season, patterns of gaps between early storms and the heaviness of the first falls, correlations between thresholds, spatial variation in correlation with the Southern Oscillation Index (SOI) and temporal trends in mean threshold dates. The earliest rains sufficient to cause seed germination or generate fresh fodder occur in the north-west of the Northern Territory with the average date being later to the south, east and west. Initial falls of the rainy season are heaviest, however, on Cape York Peninsula so that the time between first falls and saturation is shortest in the east. The probability of extended gaps between rainfall events increased from north to south. When the SOI is taken into account, no change in timing could be detected at the few sites with records of sufficient duration. However, because of changes in SOI frequency, rains are tending to start earlier in the drier parts of the north and north-west and later in the east. This may be because anthropogenic climate change is resulting in fewer classical El Niño Southern Oscillation events and more frequent El Niño Modoki climate anomalies.